Grid frequency control : Secondary frequency control tuning taking into account distributed primary frequency control - Agüero, Jorge Luis (2010)
A new method developed and applied to tune Secondary Control Loop (SCL) for grid frequency control is presented. The presented method is based on an equivalent representation of all active distributed Primary Control Loop (PCL) in the grid for frequency control. The characteristic of each PCL is associated to prime mover and its governors: Hydraulic, gas or steam. The equivalent model of distributed PCL takes into account all active representative composition of PCL in the grid for each typified power flow (seasons, working/not-working day, peak/valley, morning/afternoon/night, etc). By this way, each equivalent model of distributed PCL allows to find the best tuning of SCL for each typified power flow. This method was applied to tune the SCL of Yacyretá, a hydraulic power plant with 20 Kaplan turbines of 155 MW each one. Yacyretá is one of the power plants that have SCL in the “Sistema Argentino de Interconexión” (SADI), the largest power grid of Argentina.